2002
DOI: 10.1111/1475-6811.00012
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment and sexual behavior

Abstract: The relations between adult attachment processes and sexuality were examined in a community sample of 792 young adults (327 men and 465 women) from the Niagara region of Canada. Participants completed questionnaires that included Simpson's (1990) measure of adult attachment, self-reported physical attractiveness, erotophilia, and a variety of sexual behavior measures (e.g., number of sexual partners, age of first sexual experience, frequency of sexual behaviors in the past year, whether an affair had occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
203
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 222 publications
(221 citation statements)
references
References 57 publications
(74 reference statements)
15
203
0
3
Order By: Relevance
“…As shown in Study 2, this was due to security and anxiety priming causing participants to perceive sexual partners as less of a threat to their sexual health. Although the experimental designs of these studies makes them an important contribution to the attachment and sexuality literature, the meta-analytic consistency of the findings for the effects of attachment on condom use attitudes, across the three studies, makes them particularly valuable, given the conflicting findings obtained from previous correlational studies (e.g., Bogaert & Sadava, 2002;Feeney et al, 2000;Kershaw et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As shown in Study 2, this was due to security and anxiety priming causing participants to perceive sexual partners as less of a threat to their sexual health. Although the experimental designs of these studies makes them an important contribution to the attachment and sexuality literature, the meta-analytic consistency of the findings for the effects of attachment on condom use attitudes, across the three studies, makes them particularly valuable, given the conflicting findings obtained from previous correlational studies (e.g., Bogaert & Sadava, 2002;Feeney et al, 2000;Kershaw et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous research in this area, such as the work of colleagues (1999, 2000) and Bogaert and Sadava (2002), produced seemingly inconsistent findings, as some studies found anxiety to predict more negative condom use attitudes, whereas other studies found that security predicted more negative condom use attitudes. Our research suggests that both attachment security and anxiety can negatively impact condom use attitudes.…”
Section: Basic and Applied Implicationsmentioning
confidence: 99%
See 3 more Smart Citations